2007
DOI: 10.1007/s11745-007-3039-3
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome: Effects of n‐3 PUFAs on a Model of Dyslipidemia, Insulin Resistance and Adiposity

Abstract: Both genetic and environmental factors (e.g. nutrition, life style) contribute to the development of the plurimetabolic syndrome, which has a high prevalence in the world population. Dietary n-3 PUFAs specially those from marine oil (EPA and DHA) appear to play an important role against the adverse effects of this syndrome. The present work examined the effectiveness of fish oil (FO) in reversing or improving the dyslipidemia, insulin resistance and adiposity induced in rats by long-term feeding a sucrose-rich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(106 citation statements)
references
References 43 publications
4
100
0
2
Order By: Relevance
“…Interestingly, u-3 fatty acid concentration was the only dietary factor that emerged as significant in any of the regression models. Lombardo et al (37) have suggested that in a rat model, dietary polyunsaturated fatty acids may enhance insulin sensitivity, thereby improving the lipoprotein profile and decreasing CVD risk. Increased CVD risk is related to insulin resistance because it contributes to dyslipidemia (38).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, u-3 fatty acid concentration was the only dietary factor that emerged as significant in any of the regression models. Lombardo et al (37) have suggested that in a rat model, dietary polyunsaturated fatty acids may enhance insulin sensitivity, thereby improving the lipoprotein profile and decreasing CVD risk. Increased CVD risk is related to insulin resistance because it contributes to dyslipidemia (38).…”
Section: Discussionmentioning
confidence: 99%
“…There is also growing evidence from animal studies that fish oil intake increases insulin sensitivity and adiponectin levels in insulin resistant rats and mice (187,188) . In contrast, intervention studies generally show little or no effect of fish oils on insulin sensitivity and glycaemic control in human subjects.…”
Section: Insulin Sensitivity and Glycaemic Controlmentioning
confidence: 99%
“…This was more recently confirmed in a meta-analysis including 1075 type 2 diabetics, where the authors showed no effect of EPA and DHA on HbA1c, fasting glucose, fasting insulin or body weight (189) . There is growing evidence from animal and in vitro studies that both EPA and DHA, taken individually, exert an insulin-sensitising action (187,(190)(191)(192)(193) . However, the relative effect of EPA and DHA on insulin sensitivity in human subjects has been poorly investigated.…”
Section: Insulin Sensitivity and Glycaemic Controlmentioning
confidence: 99%
“…The reduced incidence of CVD among populations consuming fish-rich diets has been attributed to a greater proportion of omega-3 polyunsaturated fatty acids in fish oil (10)(11)(12). There is evidence that the type of protein in the diet may serve an important role in the secretion of insulin by the pancreas (13) and in the regulation of hepatic lipogenesis mediated by sterol regulatory element binding protein-1 (14).…”
Section: Introductionmentioning
confidence: 99%